What Clients Don't Get about My Profession: A Model of Perceived Role-Based Image Discrepancies - Vough, Heather C.; Cardador, M. Teresa; Bednar, Jeffrey S.; Dane, Erik; Pratt, Michael G. (Academy of Management Journal, 2013)
While most work on image has focused on character traits, we argue that, with respect to professions, roles represent an important, underexplored source of image. Employing qualitative data from 85 members of four professions, we identify “role-based image discrepancies”—misalignments between what professionals perceive as the content of their professional work and what they believe others think constitutes the professionals' professional work—as a salient and costly issue for professionals. Specifically, we find that professionals believe that clients' perceptions of their roles lead clients not only to devalue professions but also to have misaligned expectations about the process and outcomes of the professional-client relationship. Further, professionals perceive that these client evaluations hinder the professional-client interaction and, consequentially, lead to productivity and emotional costs. In response to the recognition of these potential costs, professionals are motivated to manage role-based images and client evaluations through specific problem-focused image management tactics. We develop a model of role-based image discrepancy management that encapsulates these findings and identify mechanisms that link role-based image discrepancies with their outcomes and with professional responses. Our findings carry theoretical and practical implications pertinent to professions, professionals, and image management.